HOW JOBS IN AGRICULTURE AND HANDICRAFT HAVE OPPORTUNITIES IN TOURISM DEVELOPMENT - Ni Made Ary Widiastini; Dini Andiani; Eddy Tri Haryanto (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2017)
This paper aims to describe a tourism industry which needs a variety of tourism products with an implication on the emergence of various forms of business opportunities with large, medium and small scales. The presence of a variety of tourists’ needs have caused a variety of tourism products too. Agriculture, animal husbandry, and handicraft which are needed by tourists are sectors which need a lot of workers as producers, distributors and sellers. In the study reported in the present paper is shown that the agricultural products of Bali cannot only be used as agro-tourism, but whose products can also be processed to become a variety of handicrafts. Similarly, animal husbandry which Balinese community people have focused on produces products that can be offered in a culinary tourism in which they are processed by using Balinese ingredients and offered in an appropriate wrapping which suits the market needs, while the specificity of Balinese culture has been able to produce a variety of forms of handicrafts the local and foreign tourists love. Through developments in the three sectors above, if the people can focus their attention on them and if the government can accommodate it that will be able to be used as an alternative solution to the national economy. Although in their actions they can only serve as sellers, as what has been the focus of street vendors, they actually act as safety valve of the government in overcoming unemployment problems and economic problems for themselves and their families. For this reason, it is expected that the government gives them a more conducive condition for the improvement of economy to be made starting from the family level, as part of the state of Indonesia.